The Incarceration of Juvenile Delinquents with Adult Offenders in Nigeria: Any Criminogenic and Developmental Needs - Ezeihuoma, Obinna Paschal; Ebulum, Genevieve Chimaoge (Advances in Social Sciences Research Journal, 2023)
Over a century ago, significant reforms in the juvenile justice system transformed the way juvenile offenders were treated. Back then, these young individuals often faced harsh conditions in adult prisons, leading to grave outcomes such as execution, injury, and abuse. While the juvenile justice system has seen improvements globally, Nigeria’s system remains largely underdeveloped. This research aims to examine the effects of incarcerating juvenile delinquents alongside adult offenders in Nigeria and to identify effective treatment options tailored to their specific needs. Currently, the Nigerian juvenile justice system does not adequately address the developmental and criminogenic needs of young offenders. Although some perceive the practice of housing juvenile offenders with adults as a means of public protection, research indicates that it is neither an effective method for reducing costs nor for achieving better overall outcomes.